Soliton confinement and the excitation spectrum of spin-peierls antiferromagnets - Affleck, I (1998)
The excitation spectrum of spin-Peierls antiferromagnets is discussed taking into acount phonon dynamics but treating inter-chain elastic couplings in mean field theory. This gives a ladder of soliton-anti-soliton boundstates, with no soliton continuum, until soliton deconfinement takes place at a transition into a non-dimerized phase.